Features of the oxidation processes and state of microcirculatory channel have persons exposed to low doses of ionizing radiation - Ya. V. Porovsky (Bûlleten' Sibirskoj Mediciny, 2012)
We have examined 36 liquidators (participants in emergency clean-up after the Chernobylnuclear accident) many years after the external γ-irradiation (on average (143.0 ± 14.0) mGy for (3.3 ± 0.8) months) and 13 workers of a typical research nuclear reactor, who were subject to chronic external γ-irradiation (on average (78.40 ± 12.21) mGy for (13.1 ± 2.2) years). The level of metabolites of lipid peroxidation (conjugated diene and triene conjugates of lipid hydroperoxides, TBA-reactive products) and the activity of catalase, superoxide dismutase, 5'-nucleotidase in blood serum were determined; changes in vessels of microcirculatory bloodstream (MCB) in skin-muscle bioptate were analyzed. Under the action of small doses of ionizing radiation, the oxidative disbalance and changes in activity of 5'-nucleotidase in blood serum сaccompanying the systematic inflammatory alteration of MCB vessels were found.